INVESTIGATING ENGLISH EDUCATION MASTER STUDENTS’ PERCEPTIONS ON THEIR SELF-EFFICACY IN ACADEMIC READING - Kristian Wijaya (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2021)
There is always a glimmer of hope for graduate university EFL students to transfigure into more proficient, confident, critical, and autonomous readers when they fully entrench robust self-efficacy construction at the onset of pain-staking L2 academic reading enterprises. self-efficacy can transform EFL students to be more persistent, resilient, and innovative L2 readers adaptable to fluctuating reading learning situations. This qualitative study was plied to investigate English Education Master Students’ perceptions of their self-efficacy in academic reading. Qualitative content analysis was harnessed to obtain more overarching depictions out of the specific phenomenon undergone by the participants. 31 English Education Master Students derived from batch 2019 and 2020, Sanata Dharma University also took part in this qualitative study to fill out the online Likert-scale questionnaire, and 3 out of these research participants were also invited to further participate in the open-ended interview activities. Two major findings were generated by this study namely: (1) Self-efficacy enables graduate university EFL students to be more proficient L2 readers, and (2) The lower inducement of self-efficacy may create pessimistic and struggling L2 readers.